Публічне адміністрування в органах Національної поліції: об’єктно-суб’єктний підхід - Бугайчук, К. Л.; Bugaychuk, K. L.; ResearcherID: I-5612-2016; Костянтин Бугайчук (Форум права. - 2017. - № 5. - С. 64–72, 2017)
Наведені основні напрями публічного адміністрування в органах Національної поліції та його безпосередні об’єкти. Увагу приділено правовій категорії «суб’єкт публічного адміністрування», досліджені їх види та повноваження стосовно системи органів Національної поліції. Наголошено на дуалістичному об’єктно-суб’єктному становищі деяких суб’єктів здійснення публічного адміністрування в органах Національної поліції України.

In the article the author made a scientific analysis of the content of public management in the bodies of the National Police of Ukraine, defined its features and the purpose of implementation. The main directions of public management in the bodies of the National Police, its immediate objects are given. This directions of public management in the bodies of the National Police can be defined: 1) the construction and further optimization of its organizational structures; 2) development and improvement of internal public relations in the police system regarding the implementation of relevant management procedures. As an appropriate management process in the bodies of the National Police, public management consists of two subsystems: the manager – the subject of management, and the object of management. The immediate objects of public management in the bodies of the National Police are: 1) the organizational structure of the National Police of Ukraine; 2) management procedures arising within the bodies of the National Police of Ukraine (strategic planning, development and implementation of management decisions, accounting, control, analysis of current and prospective activities); 3) organizational relations and interrelations between elements of the National Police system (coordination, subordination, delineation of powers, etc.) 4) security procedures for public management (normative, methodical, personnel, information, documentary). Particular attention is paid to the legal category of «subject of public management», their types and powers regarding the system of the bodies of the National Police are investigated. The dualistic object-subject position of some subjects of public management in the bodies of the National Police of Ukraine was noted.

Приведены основные направления публичного администрирования в органах Национальной полиции, его непосредственные объекты. Внимание уделено правовой категории «субъект публичного администрирования», исследованы их виды и полномочия относительно системы органов Национальной полиции. Отмечено дуалистическое объектно-субъектное положение некоторых субъектов осуществления публичного администрирования в органах Национальной полиции Украины.
Public Management in the National Police: an Object-Subject Approach
Публичное администрирование в органах Национальной полиции: объектно- субъектной подход
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; публічне адміністрування; суб’єкт адміністрування; об’єкт адміністрування; публичное администрирование; субъект администрирования; объект администрирования; public management; subject of management; object of management